1972
DOI: 10.1017/s0022112072000898
|View full text |Cite
|
Sign up to set email alerts
|

Convection in boxes: experiments

Abstract: Convective motions in rectangular boxes with one side horizontal have been studied. The critical Rayleigh numbers were determined. In most cases cell patterns with rolls parallel to the shorter side wall of the rectangular box were observed. The results have been compared with the known theoretical results of Davis (1967). In general, good agreement has been found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
38
2
1

Year Published

1974
1974
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(51 citation statements)
references
References 5 publications
10
38
2
1
Order By: Relevance
“…He found that the rolls always form parallel to the shorter walls of the box, and when the gap thickness is less than the other dimensions of the box the rolls are of nearly square cross-section. These results were confirmed experimentally by Stork & Muller (1972). It was found in our studies that, in a manner similar to the three-dimensional box, the transverse vortices in the upper part of the moderate-gap annulus set-up parallel to the endwalls which form the shorter sides of the upper region of the annulus.…”
Section: Moderate-gap Annulus With Airsupporting
confidence: 87%
See 1 more Smart Citation
“…He found that the rolls always form parallel to the shorter walls of the box, and when the gap thickness is less than the other dimensions of the box the rolls are of nearly square cross-section. These results were confirmed experimentally by Stork & Muller (1972). It was found in our studies that, in a manner similar to the three-dimensional box, the transverse vortices in the upper part of the moderate-gap annulus set-up parallel to the endwalls which form the shorter sides of the upper region of the annulus.…”
Section: Moderate-gap Annulus With Airsupporting
confidence: 87%
“…The cross-section of the vortices is similarly nearly square. Stork & Muller (1972) observed experimentally that an even or odd number of rolls can form in the rectangular box, but an even number is preferred. In the moderate-gap annulus, however, our numerical results indicate that only an even number of vortical cells form between the cells located at the endwalls.…”
Section: Moderate-gap Annulus With Airmentioning
confidence: 99%
“…On the other hand spatial structures of decreasing symmetry are observed, depending on both the Rayleigh number (the constraint or control parameter related to the temperature gradient) and the Prandtl number [3][4][5][6]. However [7,8].…”
mentioning
confidence: 99%
“…electronic cooling, double-pane windows, heating and cooling of buildings, refrigerators, room ventilating, heat exchangers, solar collectors, environmental phenomena and so on. Several research are oriented toward the study of rectangular enclosures wherein the heat flow is typically unidirectional, i.e., the buoyancy is induced by imposing a heating either from the side or from below, as also performed in the general review works on natural convection in closed cavities by Stork et al [1] Ostrach [2], De Vahl Davis et al [3], Khalifa Bdul-Jabbar [4] and Oztop et al [5].…”
Section: Introductionmentioning
confidence: 99%